Ratings of Essentialism for Eight Religious Identities - Toosi, Negin R. (The international journal for the psychology of religion, 2011)
As a social identity, religion is unique because it contains a spectrum of choice. In some religious communities, individuals are considered members by virtue of having parents of that background, and religion, culture, and ethnicity are closely intertwined. Other faith communities actively invite people of other backgrounds to join, expecting individuals to choose the religion that best fits their personal beliefs. These various methods of identification influence beliefs about the essentialist nature of religious identity. Essentialism is when social groups are considered to have deep, immutable, and inherent defining properties. In this study, college students (N = 55) provided ratings of essentialism for eight religious identities: Atheist, Buddhist, Catholic, Hindu, Jewish, Muslim, Protestant, and Spiritual-but-not-religious. Significant differences in essentialism were found between the target groups. Results and implications for intergroup relations are discussed.